DNA barcoding and phylogenetic relationships of ten butterfly caterpillars (Asian-Australasian Journal of Bioscience and Biotechnology, 2023)
Cytochrome C oxidase subunit I (COI), known as DNA barcodes, can be employed for the identification of an unknown specimen at the species level. The present study was aimed at performing COI gene-based identification of butterflies using butterfly caterpillars. Consecutively, ten caterpillars of ten different butterfly species from the families Papilionidae, Nymphalidae, Pieridae, Lycaenidae, and Hesperiidae were taken from respective host plants and used to generate COI gene sequences that were about 650 bp long. After BLAST analysis, the sequenced gene revealed 96–100% similarity to the same species from different regions. Then, sequences were submitted to NCBI's GenBank and obtained ten accession numbers. In order to elucidate genetic diversity and evolutionary relationships among ten species of butterfly caterpillars, pairwise distance analysis and the construction of a phylogenetic tree were performed using MEGA10 and BioEdit software. In the analysis, the interspecific genetic divergence among the caterpillars of butterflies was between 0.101-0.164%. A phylogenetic tree was constructed with the assistance of the Neighbor-Joining (NJ) algorithm, which identified two major clades, A and B, as well as indicated that butterflies caterpillars shared a common ancestor. All the species are included in these two clades, except Catopsilia pomona. This species is under the family Pieridae, and the phylogenetic position of Pieridae compared to other butterfly families is ambiguous, necessitating additional research to resolve this issue. The study demonstrated the general applicability of DNA barcoding for rapidly and accurately distinguishing butterfly species, even when using larval stages, as in the present study. Furthermore, it may disclose a higher taxonomic hierarchy of butterfly families.Asian Australas. J. Biosci. Biotechnol. 2023, 8(3), 49-55